Eksistensi Gerakan Ekonomi Koperasi BMT Nahdhatul Ummah Dalam Ekonomi Keluarga Islam - Mughni, Abdul; Mudzakir, Muhammad Agung (Jurnal Hukum Ekonomi Syariah, 2018)
The purpose of this study is to know what strategies BMT Nahdhatul Ummah Cooperative uses to word off the Emok Bank movement and to better understand the Islamic law’s view of the Emok Bank. The method used is a qualitative method with a descriptive approach, one that gives direct thought and gives descriptive description. The data in this study is obtained through interviews, documentary, observation, and library studies. The results of this study show that BMT Nahdhatul Ummah Cooperative’s which in turn blocked the Emok Bank movement is more focused on implementing sharia, providing socialization, teaching cooperative members, using system for lightweight produce and security, products vary especially by products and door to door services. In practice, the bank’s use of a joint loan system in return causes many problems, whether internal or external conflict and the interest benefits only one side. According to the Islamic view, it is because the Emok Bank uses the interest system on its loan and has more negative effects than positive effects. So this Islam forbids it according to what God says in the al-Quran and what the prophet prophets in his hadis.